PSİKOLOJİK HARBİN YENİ YÜZÜ: HOLOGRAM ASKERLERDEN YAPAY ZEKÂYA ULUSDEVLETLERİN DİRENCİ (TÜRKİYE NE YAPMALI?) - Karacam, Giirkan (TURAN : stratejik arastirmalar merkezi, 2025)
This article aims to go beyond classical warfare paradigms and delve deeper into the nature of contemporary psychological warfare methods and their role in the international power struggle. Hologram soldier projects, media manipulation, artificial intelligence-supported propaganda tools, neuroscientific techniques, mental coding injected into the education system and cultural infiltration disguised as "humanitarian aid" constitute the new arsenal of psychological warfare and threaten the sovereignty of nation-states. By analyzing the strategic fiction of these US-based practices, the national resistance strategies that Turkey should develop against this hybrid threat are evaluated in a multi-dimensional manner.